P1506IMPROVEMENTS IN MICROVASCULAR AND MACROVASCULAR DIABETES-RELATED COMPLICATIONS IN DIALYSIS PATIENTS. (6th June 2020) - Dea, Kofod; Almdal, Thomas Peter; Sørensen, Vibeke Rømming; Feldt-Rasmussen, Bo; Hornum, Mads
Abstract: Background and Aims: Newer data suggests that there has been a substantial reduction in the incidence of diabetic complications over the past 30 years. However, little is known about whether this reduction also applies to patients with diabetes and end stage renal disease. The present study examined the current prevalence and the changes in microvascular and macrovascular diabetes-related complications in dialysis patients. Method: The study was carried out as a cross-sectional study of all 119 diabetic patients in chronic dialysis at our department during June 2019. Data on diabetes-related complications was obtained from the patients' electronic medical records and compared with a historic control group of all 38 diabetic dialysis patients examined in 2004. Results: Currently, 12.3% had foot ulcer, while 40.3% had a history of foot ulcer. Lower extremity amputations were seen in 19.3%, with 7.6 % being amputated above-knee level. Development of Charcot foot was seen in 3.4%, and 64.1% had diabetic retinopathy (27.2% with proliferations), 27.2% had maculopathy, and 18.4% had a visual acuity lower than 0.3. A total of 31.1% had atrial fibrillation or flutter, 14.3% had angina pectoris and 20.2% had a history of myocardial infarction. A history of stroke or transient ischemic attack was observed in 21.8% and 6.7%, respectively. Compared with data from the 2004 cohort, we found a significant reduction in the prevalence of current foot ulcers (p=0.013), proliferative retinopathy (p=0.007) and visual acuity lower than 0.3 (p=0.028). Conclusion: The findings of this study indicate that there has been a reduction in current foot ulcers and eye complications over the past 15 years among diabetic dialysis patients, whereas the prevalence of amputations, cardiovascular and cerebrovascular complications remains high.